The Phonetics and Semantics of Repetitions in “Don’t Steal the Sun from us” by Abraham Almoqademe - Amin nazari Terizi; Mohammad Khaqani Isfahani; fazllollah mirghaderi (دراسات فی اللغه العربیه و آدابها)
Repetition is a stylistic phenomenon in literary texts and plays a prominent role in the phonological and semantic structure. Abraham Almoqademe is a resistance poet who uses repetition as a stylistic device in his poems. In this study, we survey his employment of the repetition of letters and words and sentences in the court "don’t steal the sun" as strategies to convey meaning and rhythm. We also describe the most important aspects of repetitions in this poem, relying on statistics and stylistic analysis.  Repetition is worth researching because it is one of the most important characteristics which Palestinian resistance poems are recognized by. By surveying repetition, we intend to understand the technical and aesthetic aspects this poetic text. The findings of this study show that repetitions in this poem are both simple and compound repetitions. Simple repetitions are the repetition of sounds and words while compound repetitions are the repetition of sentences. in the Moqademe’s poem, repetitions are not random and accidental but they are is purposely and systematically harmonized with the music and meanings in the poem in order to demonstrate his love of Palestine, express his sorrow for tragedies and the loss of relatives and friends, and blow invigorate the spirit of resistance and revolt against the occupation.